The 16S rRNA Analysis and Enzyme Screening of Bacillus from Rhizosphere Soil of Lombok Island - Tri Ratna Sulistiyani; Mia Kusmiati; Gita Azizah Putri (Jurnal Ilmu Pertanian Indonesia, 2021)
Bacillus are commonly found in nature, especially in soil and food. It has the ability to produce bioactive compounds as well as the enzyme. This study was aimed to isolate, identify, and screen their enzyme activities. Four soil samples from Mandalika, Lombok Island, West Nusa Tenggara (NTB), were used for isolation. Bacillus was isolated using the heat-shock method and characterized through Gram staining, endospore staining, and morphological phenotype. Bacillus identification was conducted based on 16S rRNA gene sequence. The hydrolytic enzyme activities were checked qualitatively using selective media, and the enzyme tested including amylase, galactosidase, lipase, protease, and cellulase. As many as twenty-two bacteria isolates were obtained from four soil samples and represented 15 distinct species. The member of bacteria genera successfully identified, consisted of Bacillus sp., Brevibacillus sp., and Fictibacillus sp. Bacillus sp. was the most isolated. Some of the isolated bacteria have the ability to produce lipase, protease, and cellulase that potential to be used in biotechnology processes. Keywords: Bacillus, hydrolytic enzymes, identification, screening